PENGARUH OPINI AUDIT, UMUR PERUSAHAAN DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT REPORT LAG - Nova Aristianti; Anisa Anisa (Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine and obtain empirical evidence of the influence of audit opinion, company age and the complexity of company operations on audit report lag. This type of research is quantitative research using secondary data. The population in this study is 105 financial sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique uses purposive sampling so that 76 sample companies were obtained. The data analysis technique in this study uses panel data regression analysis with the help of Eviews 9 software. The results of this study show that simultaneously audit opinions, company age and complexity of company operations affect audit report lag. And partially, only the complexity of the company's operations has an effect on the audit report lag, while the audit opinion and the age of the company have no influence on the audit report lag.